2000
DOI: 10.1074/jbc.c000671200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Recombinant Expression of a Structurally Novel Human Secreted Phospholipase A2

Abstract: Mammals contain a diverse set of secreted phospholipases A 2 (sPLA 2 s) that liberate arachidonic acid from phospholipids for the production of eicosanoids and exert a variety of physiological and pathological effects. We report the cloning, recombinant expression, and kinetic properties of a novel human sPLA 2 that defines a new structural class of sPLA 2 s called group XII. The human group XII (hGXII) cDNA contains a putative signal peptide of 22 residues followed by a mature protein of 167 amino acids that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
153
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 34 publications
(41 reference statements)
3
153
0
4
Order By: Relevance
“…Briefly, assay mixtures (1 ml) contained 100 mM TrisHCl (pH 7.0), 10 mM CaCl 2 , [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleate-labeled E. coli (Ϸ10,000 cpm), and 5 l of cell supernatants, which produces less than 5% of substrate hydrolysis. Reaction mixtures were incubated for 30 min at 37°C in a thermomixer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, assay mixtures (1 ml) contained 100 mM TrisHCl (pH 7.0), 10 mM CaCl 2 , [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleate-labeled E. coli (Ϸ10,000 cpm), and 5 l of cell supernatants, which produces less than 5% of substrate hydrolysis. Reaction mixtures were incubated for 30 min at 37°C in a thermomixer.…”
Section: Methodsmentioning
confidence: 99%
“…When exogenously added to other cell types, sPLA 2 -IB was also found to activate the expression of a number of pro-inflammatory genes including cyclooxygenase-2 (20,21), sphingomyelinase, and ceramidase (22). On the other hand, exogenously added sPLA 2 -IIA can induce the activation of cPLA 2 and cyclooxygenase-2 (3,23,24), the release of elastase (25) and ␤-glucuronidase (26), and the expression of Mac-1 (27), , CD-69 (28), inducible nitricoxide synthase (29), and Fas ligand (23) on different cell types. The nature of the sPLA 2 -IIA cellular target involved in these biological effects remains, however, to be clearly identified.…”
mentioning
confidence: 99%
“…The sPLA 2 s form a growing family of enzymes that catalyze the hydrolysis of the sn-2 ester bond of glycerophospholipids, leading to the production of free fatty acids and lysophospholipids that serve as precursors for a variety of lipid-derived mediators involved in numerous biological activities (5,6). To date, 10 different sPLA 2 s, referred to as groups IB, IIA, IIC, IID, IIE, IIF, III, V, X, and XII, have been characterized in mammals (7)(8)(9)(10)(11)(12). Of particular interest, levels of sPLA 2 activity in bronchoalveolar lavage fluids (BALF) of patients with ARDS often correlate positively with the severity of the disease (13).…”
Section: Inhibitory Effects Of Surfactant Protein a On Surfactant Phomentioning
confidence: 99%
“…Generation of Recombinant sPLA 2 Proteins-Recombinant human GIIA, GIIF, GX, and GXII sPLA 2 were produced by refolding the inclusion body protein obtained from expression in E. coli, as described previously (17,26,30,54). The preparation of recombinant human GIB, GIIE, and GV sPLA 2 will be reported elsewhere.…”
Section: Rna Extraction and Reverse Transcription-ficoll-enriched Or mentioning
confidence: 99%
“…One study identified GX sPLA 2 mRNA in peripheral blood leukocytes (25), whereas two others did not (17,29). Transcripts for GXII sPLA 2 were identified in multiple tissues, including myocardium, skeletal muscle, kidney, pancreas, and type 2 helper T cells (30,31).…”
mentioning
confidence: 99%